Perbandingan Profil Hakikat Sains pada Buku Teks IPA SMP Indonesia, Malaysia, dan Singapura: Kasus Materi Kelistrikan - Putra Habib Dhitareka; Arif Hidayat; Parsaoran Siahaan (Jurnal Penelitian Pendidikan IPA, 2022)
Nature of Science is a significant element in science education, especially for the linkages to scientific literacy. As one of an educational support for both teachers and students, textbooks become crucial for teaching and learning. Textbooks may elicit NOS understanding for students and guide teacher to deliver NOS understanding. The way to make better process and outcome, integration of NOS into the textbooks comprehensively is crucial. To get a better understanding of NOS within the diverse framework, an inclusive framework is needed to get better understanding, thus, Family Resemblance Approach is chosen. This study aims to identify the profile of NOS integration and NOS quality in secondary science textbooks by comparing different textbook from three neighboring countries (Indonesia, Malaysia, and Singapore). Descriptive research design with content analysis method conducted to identify the documents using the Family Resemblance Approach to NOS as the analytical framework. The results show that Indonesian textbooks presenting most abundance of NOS, but contain most materials delivered and the quality is mainly at low level. Malaysian textbooks contain the least representation but contain well proportion for the quality and materials presented. Singapore textbooks is least materials with abundance of NOS and consist of high-level quality of NOS. This may lead the conformity of the significance of textbooks elicited students understanding of NOS